A maternal dorsoventral prepattern revealed by an asymmetric distribution of ventralizing molecules before fertilization in Xenopus laevis - Castro Colabianchi, Aitana M.; González Pérez, Nicolás G.; Franchini, Lucía F.; López, Silvia L. (Frontiers in Cell and Developmental Biology, 2024)
The establishment of the embryonic dorsoventral axis in Xenopus occurs when the radial symmetry around the egg’s animal-vegetal axis is broken to give rise to the typical symmetry of Bilaterians. We have previously shown that the Notch1 protein is ventrally enriched during early embryogenesis in X. laevis and zebrafish and exerts ventralizing activity through β-Catenin destabilization and the positive regulation of ventral center genes in X. laevis. These findings led us to further investigate when these asymmetries arise. In this work, we show that the asymmetrical distribution of Notch1 protein and mRNA precedes cortical rotation and even fertilization in X. laevis. Moreover, we found that in unfertilized eggs transcripts encoded by the ventralizing gene bmp4 are also asymmetrically distributed in the animal hemisphere and notch1 transcripts accumulate consistently on the same side of the eccentric maturation point. Strikingly, a Notch1 asymmetry orthogonal to the animal-vegetal axis appears during X. laevis oogenesis. Thus, we show for the first time a maternal bias in the distribution of molecules that are later involved in ventral patterning during embryonic axialization, strongly supporting the hypothesis of a dorsoventral prepattern or intrinsic bilaterality of Xenopus eggs before fertilization.